Azerbaijan’s Foreign Policy : What Role for the West in the South Caucasus? - Valiyev, Anar (My University, 2017)
Since gaining independence twenty-five years ago,Azerbaijan has pursued three major foreign policy goals:resolution of the Karabakh conflict based on the territorial integrity of the country; preservation of its own independence and security; and finally becoming the major regional player by using its energy and geographical positions. Azerbaijan’s foreign policy actions may be considered a kind of “silent diplomacy,” which Baku is using to gradually develop Azerbaijan’s role in the region, playing off of contradictions among other powers. During this time, Baku has taken some bold actions that indicate its policy is not dependent on regional powers and that its interests are to be taken into account. Today, looking at the fast-changing situation in the region, we can conclude that none of these goals have been fulfilled completely. In fact, the country is facing more challenges than before. The Karabakh conflict remains one of the most problematic issues.In terms of security and trade, Azerbaijan is still struggling to find its place in the mosaic of such institutions as the EU and the Eurasian Economic Union.In addition,the sudden drop in oil prices and the inability of the country to create a diverse economy has become another headache for the political establishment. Moreover, the lack of needed investments decreases the chances that the country will become a regional hub.This chapter reviews current problems challenging the country and recommends ways the transatlantic community can deal with Baku on pressuring issues.
Eastern Voices : Europes‘s East Faces an Unsettled West
Keywords: Azerbaijan -- Foreign relations -- 1991-.; Caucasus (South) -- Foreign relations -- 1991-.; Azerbaijan -- Foreign relations -- Caucasus (South).; Caucasus (South).-- Foreign relations -- Azerbaijan.; Azerbaijan -- Geopolitics.